2021
DOI: 10.3390/economies10010001
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Demand Elasticities by Income and Prices of International Market Regions: Evidence Using Vietnam’s Data

Abstract: This study aims to determine tourism demand elasticities by income and prices of regions, as well as total international markets. It is deployed to a total of 10 major source markets and two separate regions, from Asia and intercontinental to Vietnam. The results of data analysis for the period 1995–2019 and using a nonlinear panel ARDL approach show that tourism demand from major Asian markets to Vietnam is strongly income elastic, but tourism demand from major intercontinental markets to Vietnam is relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The effect of CPI on the Tourism may indicate the influence of price on the number of tourists in each region. This relationship from CPI to TR conformed with the findings of Nguyen (2022) and Praditthong et al (2022) who detect this direction of the relationship in Vietnam and Chiang Mai. According to the property of CPI which represents the price in the overall, the increasing of CPI may rise the cost to traveling of the tourism which reduce the purchase power of tourism.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The effect of CPI on the Tourism may indicate the influence of price on the number of tourists in each region. This relationship from CPI to TR conformed with the findings of Nguyen (2022) and Praditthong et al (2022) who detect this direction of the relationship in Vietnam and Chiang Mai. According to the property of CPI which represents the price in the overall, the increasing of CPI may rise the cost to traveling of the tourism which reduce the purchase power of tourism.…”
Section: Resultssupporting
confidence: 88%
“…Besides the environment factors, the tourism demand may be considered by macro factors, such as CPI which usually use as the relative price in the tourism which usually be negative effect on the tourism demand. As the study of Nguyen (2022) in Vietnam which adapted the CPI as the relative price and found the negative effect of the factor on the tourism demand into Vietnam. Conform with the study result of Praditthong et al (2022) who found the negative effect of the relative price which be adapted by CPI on the tourism demand in Chain Mai.…”
Section: Literature Reviewmentioning
confidence: 99%